ISU GENDER, IDENTITAS DAN KULTURAL DI AFRIKA DAN TIMUR TENGAH DALAM TIGA KARYA: DREAMS OF TRESPASS, MY SALWA MY PALESTINE, INSIDE THE KINGDOM - Raghib Fadhil; Salma Fauziah Rahmalia; Salsabila Fauziyah Ihya; Nurholis (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
Abstract This study aims to uncover how the analyzed literary works present cultural issues occurring in the Middle East and Africa. "Dreams of Trespass," "My Salwa My Palestine," and "Inside the Kingdom" will explore the perspectives narrated regarding the cultural anxiety experienced by the main characters, as well as their attitudes and desires to break free from those cultural constraints. Contemporary Islamic literature in the Middle East and Africa continues to reveal the complexity of issues around themes of identity, nationalism, gender, modernity, and political resistance. Writers use literature as a medium to discuss the social and political dynamics affecting the lives of Muslim communities amid rapid global changes. They also delve into the intricate relationship between Islam, local traditions, and the challenges of modernity, creating works that are not only local in nature but also universal in their influence. Based on the analysis of "Dreams of Trespass," "My Salwa My Palestine," and "Inside the Kingdom," these works depict similar cultural issues encompassing gender inequality, family honor, identity conflicts, tensions between tradition and modernity, and nationalism. In each work, armed conflict is often a central theme, with the characters' lives being governed by strict social norms, while they struggle to find their place in a rapidly changing world. Keywords: Islamic Literature, Cutural Issues, Gender, Identity Abstrak Studi ini bertujuan untuk mengungkap bagaimana karya sastra yang diteliti menyajikan isu kultural yang terjadi di Timur Tengah dan Afrika. “Dreams of Trespass”, “My Salwa My Palestine”, “Inside the Kingdom” akan memaparkan tentang bagaimana sudut pandang Yang dinarasikan terhadap keresahan kultur yang dialami oleh tokoh utama dan bagaimana sikap dia serta keinginan untuk terlepas dari kultur tersebut. Sastra Islam kontemporer di daerah Timur Tengah dan Afrika terus hadir dengan mengungkap kompleksitas isu pada tema-tema identitas, nasionalisme, gender, modernitas, dan perlawanan politik. Penulis menggunakan sastra sebagai sarana untuk mendiskusikan dinamika sosial dan politik yang memengaruhi kehidupan masyarakat Muslim di tengah perubahan global yang cepat. Mereka juga mendalami hubungan kompleks antara Islam, tradisi lokal, dan tantangan modernitas, menciptakan karya-karya yang tidak hanya bersifat lokal tetapi juga universal dalam pengaruhnya. Berdasarkan hasil analisis pada karya “Dreams of Trespass”, “My Salwa My Palestine”, dan “Inside the Kingdom” menceritakan persamaan isu-isu kultural yang mencakup ketidaksetaraan gender, kehormatan keluarga, konflik identitas, ketegangan antara tradisi dan modernitas, serta nasionalisme. Dalam setiap karya, konflik bersenjata selalu menjadi pusat cerita, dengan kehidupan mereka dikendalikan oleh norma-norma sosial yang ketat, sementara mereka berjuang untuk menemukan tempat mereka di dunia yang sedang berubah. Kata Kunci: Sastra Islam, Isu kultur, Gender, Identitas